2019
DOI: 10.1109/access.2019.2910081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PD and Breakdown Characteristics Induced by Metal Particles and Bubbles in Flowing Transformer Oil

Abstract: Metal particles and bubbles are two typical impurities in transformer oil that can cause partial discharge (PD) and even electric breakdown. The PD characteristics are closely related to the motions of these impurities in flowing transformer oil. In this paper, the motions of impurities were obtained by a camera and a simulation model at first. Then, we employed three methods, namely, antennas, a non-inductive resistor, and the method recommended by IEC 60270, to measure the PD signals simultaneously. The brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The experi-ment setup was depicted in Figure 1, while its realization at the laboratory was shown in Figure 2. The test circuit consisted of a high voltage transformer (1), a diode (2), a smoothing capacitor (3), two measuring resistors (4), a damping resistor (5), a grounding switch (6), a set of the test object (7), an arrester tube (8), a resistor 56 Ω (9), an oscilloscope (10), a digital measuring instrument (11), and a camera (12). The specification for each component of the high voltage generator can be seen in Table 1.…”
Section: Experimental Setup Of Oil Insulation Testing With Floating Metallic Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experi-ment setup was depicted in Figure 1, while its realization at the laboratory was shown in Figure 2. The test circuit consisted of a high voltage transformer (1), a diode (2), a smoothing capacitor (3), two measuring resistors (4), a damping resistor (5), a grounding switch (6), a set of the test object (7), an arrester tube (8), a resistor 56 Ω (9), an oscilloscope (10), a digital measuring instrument (11), and a camera (12). The specification for each component of the high voltage generator can be seen in Table 1.…”
Section: Experimental Setup Of Oil Insulation Testing With Floating Metallic Particlesmentioning
confidence: 99%
“…In addition to the applied voltage type (DC, AC, or composite), liquid viscosity, and parameters related to the particles themselves, the liquid motion may affect the particle trajectories whereby the PD characteristics may be exaggerated. Recently, a research group actively investigated partial discharge activity on flowing trans-former oil contaminated by metallic particles under different operating temperatures, velocity, applied voltage, and particle concentration [11][12][13][14]. They found that the metallic particles increased partial discharge activity and lower breakdown voltage, but moving oil helped reduce partial discharge activity.…”
Section: Introductionmentioning
confidence: 99%
“…Photographing the bubble positions over time in a horizontal oil pipeline allows one to analyze how temperature and applied voltage affect the trajectory of bubbles in horizontal oil pipelines. The results show that the movement of bubbles is divided into two phases: a rising phase and a horizontal phase [17,18]. However, these studies assume a uniform electric field when discussing bubble migration.…”
Section: Introductionmentioning
confidence: 98%
“…c) Free (metal, cellulose) particles in transformer oil [10,11]. d) Gas bubbles in transformer oil [12][13][14][15][16]. e) Surface tracking on an oil-impregnated pressboard [17][18][19].…”
Section: Introductionmentioning
confidence: 99%